Midwives' experiences of referring obese women to either a community or home-based antenatal weight management service: Implications for service providers and midwifery practice. (June 2017) - Atkinson, Lou; French, David P.; Ménage, Diane; Olander, Ellinor K.
Abstract: Objective: a variety of services to support women to undertake weight management behaviours during pregnancy have recently been implemented as a means to reduce the risks to mother and infant. In the UK, midwives lead the care of the majority of pregnant women and are seen as the ideal source of referral into antenatal services. However, midwives have reported concerns regarding raising the topic of weight with obese women and negative referral experiences have been cited as a reason not to engage with a service. This study explored midwives' experiences of referring women to one of two antenatal weight management services. Design: qualitative, cross-sectional interview and focus group study, with data analysed thematically. Setting: midwifery teams in the West Midlands, England. Participants: midwives responsible for referring to either a home-based, one to one service (N=12), or a community-based, group service (N=11). Findings: four themes emerged from the data. Participants generally had a positive View of the service, but their Information needs were not fully met, as they wanted more detail about the service and feedback regarding the women they had referred. Approaches to referral differed, with some participants referring all women who met the eligibility criteria, and some offering women a choice to be referred or not. Occasionally the topic was not raised at all when a negative reception was anticipated. Reasons for poor uptake of the services included pragmatic barriers, and their perception of women's lack of interest in weight management. Key conclusions: midwives' differing views on choice and gaining agreement to refer means referral practices vary, which could increase the risk that obese women have inequitable access to weight management services. However, midwives' confidence in the services on offer may be increased with more detailed information about the service and feedback on referrals, which would additionally act as prompts to refer. Implications for practice: weight management services need to improve communication with their referral agents and try to overcome practical and psychosocial barriers to uptake. It would be beneficial to develop a shared understanding of the concept of 'informed choice' specifically regarding referral to health promotion services among midwives. Training which demonstrates effective methods of sensitively introducing a weight management service to obese women may increase midwives' confidence to consistently include this in their practice. These measures may improve women's engagement with services which have the potential to reduce the risks associated with maternal obesity. Highlights: Midwives welcomed the option to refer obese pregnant women to weight management services. Midwives were split between taking a 'refer all' or 'refer with agreement' approach. Detailed information on the service and feedback on referrals are vital. Training for midwives could facilitate women's informed decision-making.